Techniques for Producing High-Quality Tomato Seeds: OP & Hybrid Seed Production in Bangladesh - Quamruzzaman, A K M; Akter, Limu (European Journal of Applied Sciences, 2024)
The production of high-quality open-pollinated (OP) and hybrid tomato seeds in Bangladesh is essential for enhancing agricultural productivity and ensuring food security. This paper examines the specific techniques and practices tailored to the Bangladeshi context for producing superior OP and hybrid tomato seeds. For OP seeds, techniques include selecting high-yielding, disease-resistant varieties and employing traditional breeding methods to enhance local adaptability. Controlled pollination and isolation techniques prevent cross-contamination and maintain seed purity. For hybrid seeds, advanced practices such as line development, emasculation, and hybridization techniques are crucial for producing high-performance hybrids with improved traits. The paper also explores the impact of environmental conditions, soil management, and pest control specific to Bangladesh’s climate. Additionally, it addresses post-harvest practices including seed extraction, cleaning, drying, and storage to maintain seed quality and viability. By integrating these techniques with modern agricultural practices and local expertise, the paper aims to provide a comprehensive guide for optimizing tomato seed production in Bangladesh, thereby supporting sustainable agriculture and meeting market demands.